Harmonized Male/Female and Urban/Rural Subnational Expenditure, Poverty, and Inequality Indicators at 2011 PPP $1.90/day and $3.10/day for Africa South of the Sahara - International Food Policy Research Institute (International Food Policy Research Institute, 2017)
Subnational poverty headcount ratios were derived from 66 nationally representative household surveys and population census information conducted in various years around 2008 for 26 countries. Our poverty calculations are based on the comparison between the household per-capita consumption expenditure (a synthetic indicator expressing the money-metric welfare utility level) and the $1.90 and $3.10/day poverty lines expressed in international equivalent purchasing power parity (PPP) dollars in 2011. Poverty headcount with standard deviation, gap, severity, and Gini index are also provided.